Islam and capitalism: Current Islamist modernities in Turkey - Ph.D, Emre Basci, (International Journal of Scientific Research and Management (IJSRM), 2017)
The main purpose of this article is to open a discussion about the contemporary interaction of capitalismand Islam in Turkey and to come up with a brand-new typology—in political/ideological, production andconsumption contexts—as an outcome of this interesting interaction. The paper utilizes literature reviewto reach different varieties of modernity that lie at the intersection of religion and 3 mentioned contexts.Starting from the global roots of capitalistic influence on religion-related behavior, the author mainly aimsto focus on the dynamics in Turkey. The article could be deemed original as it pursues to introduce a freshclassification to business, sociology and political science literatures. The findings are expected to providereaders with research ideas about production styles, cultural consumption, and political antagonism relatedto religion and ideology